Study on S-shaped region of pump turbine based on Omega vortex analysis method and entropy production theory - Li, Zhenggui; Zeng, Hongji; Wang, Kun; Peng, Xiaodong; Yan, Shengnan; Zhao, Qin (International Journal of Agricultural and Biological Engineering, 2023)
In order to comprehensively analyze the operation instability of the pump turbine S-shaped region, this paper uses DDES turbulence model to calculate the model pump turbine from the perspective of the evolution law of runner vortex and draft tube vortex rope and entropy production rate, combined with experiments. The results show that the numerical simulation is in good agreement with the experiment. Omega vortex analysis method is more accurate than other vortex recognition methods because it is not affected by the threshold value. The vortices at the runner region under the runaway condition and the turbine brake condition develop towards the vaneless space and the blade pressure surface respectively, which will cause the flow obstruction and blade separation. The overall vorticity of the reverse pump condition is the largest. The vortex rope of the draft tube under runaway and turbine brake conditions is columnar in shape and has very high rotational strength. The vortex rope under reverse pump conditions is prone to fracture and form scattered vortices, impeding the normal movement of the fluid. The entropy production rate of the spanwise surface near the upper ring and the lower crown is greater than the middle spanwise surface due to the boundary layer effect. And the energy dissipation in the runner under reverse pump conditions is characterized by high at both ends of the runner and low in the middle. The energy dissipation near the wall of the straight cone section of the draft tube is large due to the squeezing effect of the vortex rope on the flow. Keywords: pump turbine, S-shaped region, vortex analysis method, vortex evolution, entropy production rate DOI: 10.25165/j.ijabe.20231603.7831 Citation: Li Z G, Zeng H J, Wang K, Peng X D, Yan S N, Zhao Q. Study on S-shaped region of pump turbine based on Omega vortex analysis method and entropy production theory. Int J Agric & Biol Eng, 2023; 16(3): 102–109.